From Dreams of the Worker State to Fighting Hitler: The German-Canadian Left from the Depression to the End of World War II - Grenke, Art (Labour/Le Travailleur, 1995)
German-Canadian labour first organized itself at the national level soon after the outbreak of the Depression, in 1929. Once organized, the movement was integrated into the international communist labour movement, under the direction of the Comintern. After the rise to power of Adolf Hitler in Germany, German-Canadian labour changed its focus from radically altering society to fighting Naziism. The change in focus helped many German-Canadian pro-communists escape internment when war broke out. The war, however, brought an end to their organized activities. These recommenced soon after Nazi Germany's attack on the Soviet Union. Established in 1942, the German Canadian Federation became essentially an advocate of Soviet Russian views and interests. This greatly weakened its appeal in the German Canadian community and contributed to the demise of the German Canadian labour movement soon after the end of World War Π.